The effect of aerobic virtual‐reality‐based exercise on restless legs syndrome, sleep quality, and quality of life among patients undergoing hemodialysis - Achmad Fauzi; Fatimah Ahmedy; Diana Irawati (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2024)
Background: Virtual reality (VR) therapy for hemodialysis (HD) patients can improve physical function, maintain patient compliance, and have a positive effect on functional capacity, strength, and health-related quality of life. Nevertheless, the utilization of this treatment for HD patients remains restricted, particularly in the context of Indonesia where its development has yet to be established.Objectives: the primary objective of this research attempt was to determine the effect of aerobic exercise using virtual reality technology on restless legs syndrome, sleep quality, and quality of life in patients undergoing hemodialysis therapy. Methods: The present study employs a quasi-experimental design with a two-group pretest-posttest design. The inclusion criteria for this study include of patients with HD who are over the age of 20, have been undergoing hemodialysis for a minimum of 6 months, exhibit cooperative behavior and compositional awareness, and express a willingness to participate as respondents. The KDQOL-SF, IRLSG Scale, and PSQI were used to measure study outcome.Results: There were 95 people that could have participated, but only 75 ended up doing so due to exclusions and dropouts. The intervention significantly decreased RLS score and improved sleep quality, but quality of life did not increase significantly. In the control group, RLS score did not decrease significantly, sleep quality did not improve, and quality of life did not increase significantly.Conclusion: Intradialytic aerobic exercise supported with virtual reality may have additional effects in RLS, sleep quality, and quality of life. Further research is needed to assess the effect of VR-based intervention, both alone and when combined with other therapies.